A Review of Reagents for Fluorescence Microscopy of Cellular Compartments and Structures, Part II: Reagents for Non‐Vesicular Organelles. Issue 1 (16th February 2018) - Kilgore, Jason A.; Dolman, Nick J.; Davidson, Michael W.
Abstract: A wide range of fluorescent dyes and reagents exist for labeling organelles in live and fixed cells. Choosing between them can sometimes be confusing, and optimization for many of them can be challenging. Presented here is a discussion on the commercially‐available reagents that have shown the most promise for each organelle of interest, including endoplasmic reticulum/nuclear membrane, Golgi apparatus, mitochondria, nucleoli, and nuclei, with an emphasis on localization of these structures for microscopy. Included is a featured reagent for each structure with a recommended protocol, troubleshooting guide, and example image. Curr. Protoc. Cytom . 66:12.31.1‐12.34.24. © 2013 by John Wiley & Sons, Inc.